2012
DOI: 10.1021/jp2081758
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Diffusion Coefficient and Ionic Conductivity of CO2 in Aqueous Ionic Solutions

Abstract: Mass diffusion coefficients of CO(2)/brine mixtures under thermodynamic conditions of deep saline aquifers have been investigated by molecular simulation. The objective of this work is to provide estimates of the diffusion coefficient of CO(2) in salty water to compensate the lack of experimental data on this property. We analyzed the influence of temperature, CO(2) concentration,and salinity on the diffusion coefficient, the rotational diffusion, as well as the electrical conductivity. We observe an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 51 publications
4
31
0
Order By: Relevance
“…Under these circumstances, it can be appropriate to consider the tracer diffusion coefficient of the sparingly soluble component in an otherwise spatially uniform brine that is treated as a pseudopure solvent. Such a reduction has been discussed by Garcia-Rateś et al, 4 using arguments based on the Stefan-Maxwell formalism, and also by Cussler. 5 Thus, in the remainder of this work, we focus on the diffusion coefficient D 11 coupling the flux and concentration gradient of component 1, CO 2 , and denote this simply by D. The main assumptions in applying such a treatment are that the concentration of solute 1 is so low that there is negligible diffusional coupling with other solutes and that interactions between component 1 and the other solutes are negligible, in which case D ij ≈ 0 when i ≠ j.…”
Section: Introductionmentioning
confidence: 90%
“…Under these circumstances, it can be appropriate to consider the tracer diffusion coefficient of the sparingly soluble component in an otherwise spatially uniform brine that is treated as a pseudopure solvent. Such a reduction has been discussed by Garcia-Rateś et al, 4 using arguments based on the Stefan-Maxwell formalism, and also by Cussler. 5 Thus, in the remainder of this work, we focus on the diffusion coefficient D 11 coupling the flux and concentration gradient of component 1, CO 2 , and denote this simply by D. The main assumptions in applying such a treatment are that the concentration of solute 1 is so low that there is negligible diffusional coupling with other solutes and that interactions between component 1 and the other solutes are negligible, in which case D ij ≈ 0 when i ≠ j.…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, the assumption that infinite-dilution CO 2 diffusivity will accurately predict the diffusivity of CO 2 in GCS reservoirs 3,4 has never been experimentally tested. To clarify the diffusion behavior of CO 2 under realistic reservoir conditions, and to pursue a research program on fluid and mineral reactions relevant to GCS, we have constructed a Raman microscope that is compatible with high-pressure, hightemperature capillaries and microfluidic cells that operates routinely up to 100 bar and 80°C with imaging capabilities at diffraction-limited spatial resolution (i.e., ∼300 nm).…”
Section: ■ Introductionmentioning
confidence: 99%
“…27 Additionally, Vlcek et al 27 28 reported a fairly good agreement with the experimental values and showed a dependence of CO 2 diffusivity on the isotopic mass of the carbon atom. Finally, Garcia-Rateś et al 29 reported values for the diffusivity of CO 2 in H 2 O for a narrow range of temperatures and pressures; their study aimed at the determination of D CO 2 in brines.…”
Section: Introductionmentioning
confidence: 99%